Local economic development and poverty reduction in developing societies: The experience of the ILO decent work project in Ghana. (August 2019) - Azunu, Richardson; Mensah, James Kwame
There have been series of contest analysis of developmental role of international development partners in sub-Saharan Africa. However, evidence abound that whiles international development partners have over the past three decades participated actively in local economic development the academic literature has barely focused on this area. As a result, very little is known about how development partners-led local economic development has translated into poverty reduction and economic prosperity. Through a qualitative case study of ILO decent work project in Ghana, this study provides empirical assessment and impact of development partners' role in conceptualising, implementing and monitoring local economic development interventions in sub-Saharan Africa. The findings show that ILO decent work project has led to the creation of jobs, enabled participants to improve their businesses, improve their economic situation and meet their health needs and also adopt strategies to pull themselves out of poverty. The outcome of this paper is useful for both national and international development agencies in their attempt to improve societal development.